UJI AKTIVITAS BUAH MAHKOTA DEWA (PHALERIA MACROCARPA) SEBAGAI ANTIMALARIA PADA MENCIT YANG DIINFEKSI PLASMODIUM BERGHEI - Juniantara, I Kadek Ade; Laksemi, Dewa Ayu Agus Sri; Damayanti, Putu Ayu Asri; Diarthini, Ni Luh Putu Eka (E-Jurnal Medika Udayana; Vol 11 No 12 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i12.P15, 2022)
Malaria is a parasitic infection caused by Plasmodium sp. Malaria’s medication and prevention are known, but there is a problem of increasing Plasmodium resistance to antimalarial drugs such as drugs from the chloroquine class, to overcome this problem traditional medicine is chosen because it is safer and cheaper. God’s crown (Phaleria macrocarpa) is one of the plants commonly used for traditional medicine which contains several active substances, namely saponins, polyphenols, flavonoids, tannins, sterols, alkaloids and terpenoids which have potential as antimalarials which can be proven by observing the degree of parasitemia in the mice blood. This study was conducted in vivo using the Randomized Post Test Only Controlled Group method using 24 samples of mice which were divided into 4 groups. The negative control group was only 0.2 ml of RPMI as a treatment control and the treatment group was treated with God’s crown extract at doses of 1, 10, and 100 mg/kgBW, then the degree of parasitemia was examined in each mouse. The data analysis technique used is One Way ANOVA and Post Hoc test. The results obtained mean the degree of parasitemia in the control group, doses of 1 mg/kgBW, 10 mg/kgBW and 100 mg/kgBW respectively 41.70; 37.96; 31.55; and 37.0. The results based on the analysis using One Way ANOVA posttest, it was found that there were significant differences between the control group and treatment groups 1,2, and 3 with p value of 0.000 (p < 0.05). The results showed that the extract of the fruit of the God’s crown (Phaleria macrocarpa) could inhibit the growth of Plasmodium berghei, the best dose was found at a dose of 10 mg/kgBW.